2010
DOI: 10.1051/0004-6361/200913098
|View full text |Cite
|
Sign up to set email alerts
|

Abundance anomaly of the13C species of CCH

Abstract: Aims. We have observed the N = 1−0 lines of CCH and its 13 C isotopic species toward a cold dark cloud, TMC-1 and a star-forming region, L1527, to investigate the 13 C abundances and formation pathways of CCH. Methods. The observations have been carried out with the IRAM 30 m telescope. Results. We have successfully detected the lines of 13 CCH and C 13 CH toward the both sources and found a significant intensity difference between the two 13 C isotopic species. The [C 13 CH]/[ 13 CCH] abundance ratios are 1.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
85
1

Year Published

2010
2010
2025
2025

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 72 publications
(96 citation statements)
references
References 37 publications
(53 reference statements)
9
85
1
Order By: Relevance
“…The neutral-neutral reaction between C and CH 2 also contributes to forming CCH especially in moderately shielded regions. This route has been confirmed by the recent measurements of Sakai et al (2010), who obtained different abundances for the two isotopologues C 13 CH and 13 CCH. Since the two carbon atoms play equivalent roles in the photodissociation of acetylene and in the dissociative recombination of C 2 H + 2 and C 2 H + 3 , the reaction between C and CH 2 is the sole CCH formation mechanism that can produce such a difference in the C 13 CH and 13 CCH abundances because the two carbon atoms have different origins.…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…The neutral-neutral reaction between C and CH 2 also contributes to forming CCH especially in moderately shielded regions. This route has been confirmed by the recent measurements of Sakai et al (2010), who obtained different abundances for the two isotopologues C 13 CH and 13 CCH. Since the two carbon atoms play equivalent roles in the photodissociation of acetylene and in the dissociative recombination of C 2 H + 2 and C 2 H + 3 , the reaction between C and CH 2 is the sole CCH formation mechanism that can produce such a difference in the C 13 CH and 13 CCH abundances because the two carbon atoms have different origins.…”
Section: Introductionsupporting
confidence: 68%
“…This behavior can be understood since these species are closely chemically related. CCH is produced by the photodissociation of acetylene (Roberge et al 1991) and by the reaction of atomic carbon with CH 2 (Smith et al 2004;Sakai et al 2010). The dissociative recombination of molecular ions such as C 2 H 2 + and C 2 H 3 + also plays a role.…”
Section: Chemistrymentioning
confidence: 99%
“…Thus the observed CO would be tracing regions with lower 12 CO/ 13 CO ratio than the actual 12 C/ 13 C isotopic ratio. The CCH observations reported by Sakai et al (2010) toward the dark cloud TMC-1 and the star-forming region L1527 also show a 12 C/ 13 C ratio a factor of 2−4 higher than the interstellar ratio. However, the chemical fractionation claimed in their work is mostly effective at very low temperatures (T kin ∼ 10 K), while isotopic exchange reactions rates tend to balance out at higher temperatures (Woods & Willacy 2009).…”
Section: C/ 13 C Isotopic Ratio From Cch and Comentioning
confidence: 75%
“…We do not detect transitions from either the 13 CCH or C 13 CH isotopomers, which implies that the lower limits to the abundance ratios are C 2 H/ 13 CCH > 58 and C 2 H/C 13 CH > 43. Sakai et al (2010) found 13 C abundance anomalies in the 13 C-isotopomer of C 2 H toward TMC 1 and L1527, with the 13 C-species underabundant relative to the interstellar 12 C/ 13 C ratio. In addition, the two carbon atoms do not appear to be equivalent in the formation pathways of the molecule, as Sakai et al (2010) measured an abundance ratio C 13 CH/ 13 CCH = 1.6 toward both sources.…”
Section: Carbonmentioning
confidence: 90%
“…Sakai et al (2010) found 13 C abundance anomalies in the 13 C-isotopomer of C 2 H toward TMC 1 and L1527, with the 13 C-species underabundant relative to the interstellar 12 C/ 13 C ratio. In addition, the two carbon atoms do not appear to be equivalent in the formation pathways of the molecule, as Sakai et al (2010) measured an abundance ratio C 13 CH/ 13 CCH = 1.6 toward both sources. They conclude that carbon-chain molecules are not indicated to determine the 12 C/ 13 C elemental ratio, because of the positional differences and heavy 13 C dilution.…”
Section: Carbonmentioning
confidence: 90%